The Active Versus Passive Investing Debate: Evidence From the 2018-2023 Market Cycle - Prondzinski, Dale; Miller, Mitchell (Journal of Accounting and Finance, 2024)
The paper investigates the research question: Which investment management style, active or passive, produced better risk-adjusted performance from January 1, 2018, to December 31, 2023 (Prondzinski, 2010)? The comprehensive time period was further subdivided into two periods: January 2020 – May 2023, the Pandemic period, and March 2022 – December 2023, the interest rate hiking period without any interest rate cuts. The study tested twenty-seven hypotheses derived from this research question for the specified periods addressed. The study, consisting of 27 statistical tests, found that on a risk-adjusted basis, the Sharpe ratios of active indices (proxies for active management) significantly exceeded the passive indices (proxies for passive management) in nine of the periods tested) (Prondzinski, 2010).